2018
DOI: 10.12688/wellcomeopenres.13199.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of innate lymphoid cell populations at different sites in mice with defective T cell immunity

Abstract: Background: Innate lymphoid cells (ILCs) have now been identified within most tissues of the body and current evidence indicates that this family of cells play a fundamental role in maintaining tissue homeostasis. However, few studies have compared the ILC populations between several tissues. Methods: We sought to generate a comprehensive characterisation of the ILC populations in different tissues of C57BL/6 WT and genetically modified mice targeting costimulatory pathways, using transcription factor expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…Notably, a population of ILC based on IL-7Rα expression in the absence of expression of an extensive panel of lineage markers was also observed ( Fig. 1F-H), consistent with a recent report identifying such cells in multiple tissues [14]. In this report, prolonged enzymatic digestion was shown to increase the frequency of these cells prompting concerns as to their exact nature; however, here the thymus was disaggregated using only mechanical means.…”
Section: Ilc Populations In the Neonatal Thymussupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, a population of ILC based on IL-7Rα expression in the absence of expression of an extensive panel of lineage markers was also observed ( Fig. 1F-H), consistent with a recent report identifying such cells in multiple tissues [14]. In this report, prolonged enzymatic digestion was shown to increase the frequency of these cells prompting concerns as to their exact nature; however, here the thymus was disaggregated using only mechanical means.…”
Section: Ilc Populations In the Neonatal Thymussupporting
confidence: 90%
“…Mann-Whitney U-test (comparing two samples) or a one-way ANOVA (comparing three or more samples) was used for statistical analysis where *p < 0.05, **p < 0.01, ***p < 0.001, and ****p < 0.0001. In all graphs, the bar represents the median, n = 9 for day 1, n = 7 for day 7, n = 7 for day 14, and n = 7 for adulthood (apart from in F-H, where n = 8 for day 7 and n = 6 for day 14), with data (in panels B, C, D, E, G, H, I, and J) pooled from at least two independent experiments at each age. Full gating strategy for all flow cytometry data identifying thymic ILC populations is shown in Supporting Information of Id2 creERT2 × ROSA mT/mG mice after tamoxifen administration by oral gavage ( Fig.…”
Section: Identification Of Ilcs In the Adult Thymusmentioning
confidence: 99%
“…Under homeostatic conditions, the immune cell make-up of the mouse lung is predominantly conventional lymphocytes and myeloid cells, although NK cells and all three ILC subsets have also been identified in the airways, albeit at much lower frequencies (3, 4). The ILC2 population is thought to be tissue-resident and thus are the predominant helper-type ILCs in the steady-state mouse lung (3, 5).…”
Section: Ilcs In Lung Homeostasismentioning
confidence: 99%
“…2e), meaning that CD27 − ST2 − ILCs contain the ILC3 population but are not exclusively ILC3s. NKp46 and CCR6 have been used to classify ILC3s in small intestine preparations, but it has been shown that most ILC3s in the lung are NKp46 − , and only 20% are CCR6 + (32). We confirmed these results while trying to optimize our surface staining approach.…”
Section: Resultsmentioning
confidence: 99%